The role of the complement system in ocular diseases - Skowyra, Agnieszka; Śladowski, Dariusz; Majszyk-Ionescu, Julita; Grabska-Liberek, Iwona (Klinika Oczna / Acta Ophthalmologica Polonica, 2017)
The complement system is a group of proteins involved in the innate immune response. Its activation works as a cascade, in which each component activates the next one, and results in the formation of the membrane attacking complex initiating lytic cell death. Thus, the complement system plays an important role in immune defense against infections. The complement system is constantly activated in a healthy eye, releasing small amounts of active products. Regulatory proteins of the system maintain the low level of activation, thereby preventing autodestruction of ocular tissues. Recent studies have shown that excessive and uncontrolled activation of the complement system may play a key role as a cause of various widespread ophthalmic diseases, such as inflammatory corneal diseases, glaucoma, uveitis, and age-related macular degeneration. The article presents a review of current literature on the involvement of the complement system in the pathogenesis of the abovementioned diseases.